2017
DOI: 10.3390/met7060227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al-5Ti-0.62C-0.2Ce Master Alloy on the Microstructure and Tensile Properties of Commercial Pure Al and Hypoeutectic Al-8Si Alloy

Abstract: Al-5Ti-0.62C-0.2Ce master alloy was synthesized by a method of thermal explosion reaction in pure molten aluminum and used to modify commercial pure Al and hypoeutectic Al-8Si alloy. The microstructure and tensile properties of commercial pure Al and hypoeutectic Al-8Si alloy with different additions of Al-5Ti-0.62C-0.2Ce master alloy were investigated. The results show that the Al-5Ti-0.62C-0.2Ce alloy was composed of α-Al, granular TiC, lump-like TiAl3 and block-like Ti2Al20Ce. Al-5Ti-0.62C-0.2Ce master allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the Al-Ti-C-Ce grain refiner did not show the phenomenon of grain-refining fading. This result is related to the Ti 2 Al 20 Ce phase and [Ce] atoms coated on the surface of TiAl 3 and TiC, thus prolonging the nucleation time of the second phase in Al melt [ 16 , 23 ]. With severe grain-refining fading, the average size of pure aluminum grains increased to 116.4 μm and 68.4 μm after holding for 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Al-Ti-C-Ce grain refiner did not show the phenomenon of grain-refining fading. This result is related to the Ti 2 Al 20 Ce phase and [Ce] atoms coated on the surface of TiAl 3 and TiC, thus prolonging the nucleation time of the second phase in Al melt [ 16 , 23 ]. With severe grain-refining fading, the average size of pure aluminum grains increased to 116.4 μm and 68.4 μm after holding for 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…∆G 3 < 0, evenly distributed CeC 2 particles react to generate TiC and the released [Ce] atoms (reaction (4)) ( Figure 16 b). [Ce] atoms adsorb on the surface of TiAl 3 , and the reaction (5) forms a core-shell structure of Ti 2 Al 20 Ce coated on TiAl 3 [ 18 ] ( Figure 16 c), which inhibits the growth of TiAl 3 phase crystal nuclei and promotes α-Al nucleation [ 16 , 23 ] ( Figure 16 d). In the meantime, part of the Ti 2 Al 20 Ce phase continuously releases [Ce] atoms [ 17 ] into the melt during the holding process.…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, the layer guarantees that even tiny TiC particles cannot easily precipitate together. The uniform distribution of TiC in the aluminum melt in a suspended state not only can fully undertake the role of the nucleation core, but can also provide a good grain-refinement recession and guarantee a long-term refining effect 26,27 .…”
Section: 25mentioning
confidence: 99%
“…Moreover, the author’s previous research found that the preparation of Al-Ti-C-Ce alloy by in-situ reaction of aluminum melt with CeO 2 as an additive cannot only reduce the production cost, but also improve the refining performance of Al-Ti-C alloy [18,23]. However, the mechanism of rare earth oxides in the preparation of Al-Ti-C-RE alloys is still unclear [24,25,26,27,28], and there is a lack of systematic and in-depth research on the thermodynamics and kinetics of synthesis reactions.…”
Section: Introductionmentioning
confidence: 99%